2015
DOI: 10.1371/journal.pone.0140002
|View full text |Cite
|
Sign up to set email alerts
|

Access to Orphan Drugs: A Comprehensive Review of Legislations, Regulations and Policies in 35 Countries

Abstract: ObjectiveTo review existing regulations and policies utilised by countries to enable patient access to orphan drugs.MethodsA review of the literature (1998 to 2014) was performed to identify relevant, peer-reviewed articles. Using content analysis, we synthesised regulations and policies for access to orphan drugs by type and by country.ResultsFifty seven articles and 35 countries were included in this review. Six broad categories of regulation and policy instruments were identified: national orphan drug polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
267
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(279 citation statements)
references
References 61 publications
(256 reference statements)
5
267
1
6
Order By: Relevance
“…Product development is initiated when an application for orphan drug designation is approved, allowing the company to proceed with certain benefits and fiscal incentives, including reduction of regulatory fees, tax credit for the costs of studies, fee waivers, priority review for authorization, and 7 (USA) or 10 (Europe) years of market exclusivity per indication [3,13,14]. A recent comprehensive review showed that most European, Asian, and North American countries (27/35) had adopted orphan drug legislation [3] and that these regulations have promoted the development of orphan products [15][16][17] although some issues, pertaining to pricing, have arisen, regarding incentives given to companies that later reap huge profits [18].…”
Section: Orphan Drug Legislationmentioning
confidence: 99%
See 3 more Smart Citations
“…Product development is initiated when an application for orphan drug designation is approved, allowing the company to proceed with certain benefits and fiscal incentives, including reduction of regulatory fees, tax credit for the costs of studies, fee waivers, priority review for authorization, and 7 (USA) or 10 (Europe) years of market exclusivity per indication [3,13,14]. A recent comprehensive review showed that most European, Asian, and North American countries (27/35) had adopted orphan drug legislation [3] and that these regulations have promoted the development of orphan products [15][16][17] although some issues, pertaining to pricing, have arisen, regarding incentives given to companies that later reap huge profits [18].…”
Section: Orphan Drug Legislationmentioning
confidence: 99%
“…If the price is excessively high, availability will depend on coverage and reimbursement policies and regulations, imposed by society as well as by insurance companies. Health technology assessment (HTA), the systematic appraisal of a novel therapy and its consequences, is usually applied [3]. Governmental agencies may rely on incremental cost-effectiveness ratios (ICERs) for evaluation of drug price in relation to health benefits.…”
Section: Cost-effectiveness Of An Orphan Drugmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, orphan and ultra-orphan products (targeting diseases that affect <5 in 10,000 people [24], and ≤1 in 50,000 people [2], respectively) are required to demonstrate cost-effectiveness at the current willingness-to-pay (WTP) threshold of three times the gross domestic product (GDP) per capita per quality-adjusted life year (QALY) gained [5] (in 2015, GDP per capita was PLN46,764, or approximately €11,000 [22,25], which would translate into a WTP threshold of approximately PLN140,000 or €33,000 per QALY). This threshold appears rather stringent, given that reimbursement decisions based on clinical value and measures of innovation – rather than a formal cost-effectiveness analysis – may lead to broader coverage for orphan drugs [26], thus improving patient access. The proposed changes exempt ultra-orphan drugs from the aforementioned cost-effectiveness requirements, and focus reimbursement decisions in ultra-orphan indications on factors that may justify the drug’s price, such as clinical effectiveness [27].…”
Section: Changes To Reimbursement Policy In Generalmentioning
confidence: 99%